AYURVEDIC MANAGEMENT OF POLYCYSTIC OVARIAN SYNDROME BY PALASADI BASTI AND PATHADI CHOORNA: A CASE REPORT - Archana, *S; Laxmipriya, Dei (International Journal of Ayurveda and Pharma Research, 2018)
Polycystic Ovarian Syndrome is the most common disease in the female population among adolescence and reproductive age group mainly due to the adoption of westernized culture. Polycystic Ovarian Syndrome (PCOS) is a physiological disorder that causes many negative effects involving a variety of systems in the body, such as the endocrine, metabolic, psychological, and reproductive systems. The complex symptomatology of PCOS makes very difficult to treat as a whole. In Ayurveda also no disease can be compared directly with PCOS. Some of clinical symptoms of PCOS may simulate Granthibhoota Artava dushti and if not treated early lead to the full manifestations and complications of PCOS. A 26 year old female came to OPD of Streeroga of IPGT & RA, having the complaints of irregular cycle, weight gain and failure to conceive since 2 years of active married life with a previous history of abortion. Sonography revealed bulky ovaries with multiple small follicles. Based on clinical findings along with sonological evidences Polycystic Ovarian Syndrome was diagnosed and a treatment protocol was selected for managing the PCOS and finally to achieve conception. Palasadi basti was selected followed by Pathadi choorna orally with warm water as internal medicine. The treatment was done for 3 months and during follow up the cycles became regular and finally the patient got conceived within 2 months.